The necessity of being elsewhere: An aesthetics between perdition and salvation (Materiali di Estetica. Terza serie, 2021)
The first part of this essay introduces the concept of the wind image, to be understood as that particular artistic representation that resists the violence and noise of the real, and shows the essential left behind by time. Such an image allows one to penetrate an intimate, existential place. The work of art is born out of a dormant potentiality, which palpitates in the life of the artist like preservation and duration, waiting to find a completed form. The second part of the essay shows how this particular existential disposition may find its fullest expression in the indirect self-portrait made by the artist, bringing about de-identification and, thus, an opening towards a universal meaning. Such an image generates an absolute identity between the artist, the work and the spectator, revealing a threefold representation that lives in its promise of redemption, its beauty residing in the self-portrait that life makes of itself.
Keywords: Wind Image; Potentiality; Self-portrait